2020
DOI: 10.1021/acsomega.0c02538
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Interaction of Potassium Salts with an Ilmenite Oxygen Carrier Under Dry and Wet Conditions

Abstract: This study describes how potassium salts representative of those in bio ash affect the reactivity of the oxygen carrier ilmenite under moist and dry conditions. Ilmenite is a bench-mark oxygen carrier for chemical-looping combustion, a technique that can separate CO 2 from flue gases with minimal energy penalty. Different potassium salts were mixed with ilmenite to a concentration of 4 wt % potassium. The salts used were K 2 CO 3 , K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 42 publications
5
44
0
Order By: Relevance
“…The same phenomenon was also seen inside the red circle. Ilmenite has been previously reported to be able to interact with potassium, where iron in reduced ilmenite migrated to the outer layer and reacted with potassium to form K titanate. …”
Section: Resultsmentioning
confidence: 99%
“…The same phenomenon was also seen inside the red circle. Ilmenite has been previously reported to be able to interact with potassium, where iron in reduced ilmenite migrated to the outer layer and reacted with potassium to form K titanate. …”
Section: Resultsmentioning
confidence: 99%
“…19,28 Other studies have found that, with increased time of exposure, K migrates into the ilmenite particle core 27 and that, depending on the chemical form of K, it will react differently in the matrix. 29 Research conducted on the ash layer build-up and sulfur interaction when using ilmenite in OCAC applications shows that calcium and potassium are bound to sulfur both in and on the ilmenite particles. 27,30 Limited research around the chemistry of heavy metals in chemical looping processes is available.…”
Section: Introductionmentioning
confidence: 99%
“…It is not uncommon to combine experimental tests with thermodynamic predictions. 29,36,37 Most recent studies have used FactSage and associated databases to monitor the slag formation and predict agglomeration behavior in the CLC of coal. 38,39 It was concluded that parameters that affect the bed composition are the ash composition, the ratio of ash to OC, and the type of OC, which had a significant impact on the rate of agglomeration.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of published research on the effects of alkalis in CLC has been carried out in lab-scale investigations and has been primarily focused on the interaction of alkali-containing fuel ash components with the oxygen carriers. 24 27 Two pilot-scale investigations in continuous CLC systems have looked at effects of alkalis on oxygen carriers, 28 , 29 but only a few studies have attempted to directly measure and determine alkali release to the gas phase and alkali retention in the bed material. 30 32 …”
Section: Introductionmentioning
confidence: 99%
“…In fluidized bed biomass boilers, alkalis that are retained in the bed are known to cause bed material agglomeration that can result in operational upsets and unplanned boiler shutdowns. , The release of alkali compounds in the conventional combustion, gasification, and pyrolysis context has been studied in full scale in biomass boilers and gasifiers, in pilot-scale reactors, , at the lab scale, and through modeling work. , In CLC, the implications of alkali release from biomass fuel conversion are not yet well-explored. The majority of published research on the effects of alkalis in CLC has been carried out in lab-scale investigations and has been primarily focused on the interaction of alkali-containing fuel ash components with the oxygen carriers. Two pilot-scale investigations in continuous CLC systems have looked at effects of alkalis on oxygen carriers, , but only a few studies have attempted to directly measure and determine alkali release to the gas phase and alkali retention in the bed material. …”
Section: Introductionmentioning
confidence: 99%